Modified Asphalt Mixtures Incorporating Pulverized Recycled Rubber and Recycled Asphalt Pavement - Cubas, Marlon; Correa, Evelyn; Benavides, Wilmer; Suclupe, Robert; Arriola, Guillermo (Salehan Institute of Higher Education, 2025)
In the search to achieve eco-friendly techniques that ensure significant improvements in the properties of hot mix asphalt (HMA), recycled materials are being considered with greater application, coming from the pavement itself and also from artificial elements such as rubber. In this sense, the objective was to study the behavior of the mechanical and microstructural properties of HMA by adding pulverized recycled rubber (PRR) and recycled asphalt pavement (RAP), taking into account a control group without any addition and an experimental group with PRR and RAP. The research involved the production of briquettes with the modification of asphalt cement (AC) using doses of 3%, 5%, and 7% of PRR as a replacement by weight of AC. Then, the optimal percentage of PRR was combined with 10%, 20%, and 30% RAP as a partial substitute for the coarse aggregate. It should be noted that in both aspects, the thermogravimetric and microstructural performance of the asphalt mixture was evaluated. Subsequently, the results obtained indicate that the HMA is MAC-1 type, and it was established that the combinations of PRR and RAP significantly influence the physical-mechanical properties of the HMA with 3%PRR+10%RAP. On the other hand, the findings of the PRR thermogravimetric analysis show that the degradation of HMA occurs at 350°C, causing the loss of both mechanical and microstructural properties. However, infrared spectroscopy and scanning electron microscopy revealed that the PRR adheres correctly with the aggregate, improving the morphology and texture of the HMA. Doi: 10.28991/CEJ-2025-011-02-02 Full Text: PDF